Assessment of vaccination impact in PPR-control program implemented in southern States of India: A system dynamics model approach - Gurrappanaidu, G.; Subbanna, N.K.G.; Wanyoike, Francis N.; Bahta, Sirak T.; Reddy, Y.R.; Bardhan, D.; Vinayagamurthy, B.; Kennady, Vijayalakshmy; Rahman, Habibur (MDPI, 2025)
Mass vaccination against peste des petits ruminants (PPR) in two southern states of India, namely Andhra Pradesh and Karnataka, has reduced disease outbreaks significantly. The sporadic outbreaks reported now can be attributed in part to the recurring movement of sheep and goats between these contiguous states. This study assessed the present level of economic burden and impact of vaccination on the local system (one state), considering the exposure from the external system (neighboring state) using a system dynamic (SD) model. The SD model relies on interdependence, interaction, information feedback, and circular causality and captures potential feedback between disease control interventions and their impact on various epidemiological and economic outcomes. The data for parameterization of the model were collected through surveys, expert elicitation, and literature review. The sporadic outbreaks reported in recent years (<10 outbreaks/year during 2022) were due to continuous “mass vaccination” for more than a decade. During 2021–2022, the PPR incidence was less in both the states, with an estimated loss of USD 26.30 and USD 22.86 million in Andhra Pradesh and Karnataka, respectively. The SD model results showed a systemic increase in flock size and offtakes and a decline in the number of infected and death cases under high vaccination coverage (75% and 100% coverage) compared to the low-coverage scenario. Hence, the coordinated inter-state vaccination efforts offer better prospects, as efforts in one state have positive externalities in terms of fewer outbreaks in a neighboring state.